A comparative analysis of piezosurgery and oscillating saw for balanced orbital decompression. (2nd November 2019) - Stähr, Kerstin; Eckstein, Anja; Holtmann, Laura; Schlüter, Anke; Dendy, Meaghan; Lang, Stephan; Mattheis, Stefan
ABSTRACT: Introduction : Different minimally invasive surgical approaches to the orbit allow individualized bone resection to reduce proptosis and decompress the optic nerve in patients with Graves' orbitopathy (GO). This study aims to compare piezosurgery to an oscillating saw used to resect bone from the lateral orbital wall. Methods : In a retrospective study, we analyzed balanced orbital decompressions performed on 174 patients (318 cases) with GO. An oscillating saw was used in 165 cases (saw group) and piezosurgery in 153 cases (piezo group). Peri- and postoperative complications, reduction of proptosis, new onset of diplopia and improvement of visual acuity in cases of pre-operative optic nerve compression were analyzed. Results : We observed no significant differences in the surgical outcome between the two groups. Proptosis reduction was 4.6 mm in the saw group ( p < 0.01) and 5.3 mm in the piezo group ( p < 0.01). Intraoperative handling of the piezosurgery device was judged superior to the oscillating saw, due to soft tissue conservation and favourable cutting properties. Duration of the surgery did not differ between the groups. No serious adverse events were recorded in both groups. Conclusion : The application of piezosurgery in orbital decompression is more suitable than an oscillation saw due to superior cutting properties such as less damage to surrounding soft tissue or a thinner cutting grove.